The Complexity of Co-existing Functional Vision Loss and Organic Diagnoses. - Ansel, Tobin; Nguyen, Tam; Shenouda-Awad, Nancy; Zerilli-Zavgorodni, Theresa (Optometry & Visual Performance, 2018)
Background: Parkinson's patients commonly experience a visual midline shift that causes postural and gait changes, increasing the risk of falls. If the optometrist can improve the visual midline shift with the use of yoked prism prescriptions, the risk of falls will decline and ultimately decrease the overall potential healthcare cost. Case Report: A 77-year-old white male diagnosed with Parkinson's presented for an evaluation. The patient complained of double vision and difficulty judging space perception that was affecting his balance when walking. He was treated with a lens prescription that included a combination of yoked and base-in prisms. Conclusion: After 1 month of wearing the new prism prescription, he no longer experienced double vision and showed improved balance when walking. This case emphasizes the importance of evaluating visual midline shifts and prescribing yoked prisms in this patient population to improve overall balance and to lower the risk of falls.